Analisis risiko operasional dalam industri perbankan: studi kasus pada bank umum di indonesia - Ni’maturofi’ah, Dewi (Maliki Interdisciplinary Journal, 2025)
This study analyzes operational risks that arise in the operational activities of commercial banks in Indonesia. With the increasing complexity of operations and technological developments, commercial banks face various challenges in managing risks that can threaten their stability and performance. Operational risks that include human error, system disruptions, and external events, require serious attention for effective mitigation. This study identifies various forms of operational risks and evaluates strategies for managing these risks. Proposed solutions include improving human resources, developing better internal control systems, and implementing sophisticated information technology for risk detection and prevention. The results of the study indicate that the implementation of systematic and effective operational risk management can not only improve bank stability and profitability, but also strengthen customer trust and support the growth of the national banking sector.